Chemical Dopant‐Free Doping by Annealing and Electron Beam Irradiation on 2D Materials (Adv. Electron. Mater. 10/2021). (11th October 2021) - Choi, Min Sup; Lee, Myeongjin; Ngo, Tien Dat; Hone, James; Yoo, Won Jong
Abstract : Field‐Effect Transistor Chemical‐free and clean doping methods for 2D semiconducting materials are developed by Min Sup Choi, Won Jong Yoo, and co‐workers in article number 2100449 . The p‐ and n‐doping in 2D field‐effect transistors are observed by annealing and e‐beam irradiation, attributed to the absorption of oxygen molecules and charge trapping at the interfaces, respectively.